Arkangel : a Sigma force novel [large type] - Rollins, James, 1961- (Rollins, James, 1961- Sigma Force novel., 2024)
"The execution of a Vatican archivist within the shadow of the Kremlin exposes a conspiracy going back three centuries--to the bloody era of the Russian Tsars. Before his murder, he manages to dispatch a coded message, a warning of a terrifying threat, one tied to a secret buried within the Golden Library of Tsars, a vast and treasured archive that had vanished into history. As combative forces race for the truth behind this death and alarming discovery, Sigma Force is summoned to aid in the search--not only for this missing trove of ancient books, but to follow a trail far into the Arctic, to search for the truth about a lost continent and a revelation that could ignite a global war. But Sigma Force has its own difficulties at home after an explosive attack on the National Mall--one aimed at the heart of their covert agency--has left them vulnerable and exposed. The growing conflict--both on Russian soil and deep in the Arctic--will reignite a centuries-old war between the newly resurgent Russian Orthodox Church and the Vatican, while sabers rattle across the nations of the Arctic Circle, threatening to turn those icy seas into a fiery conflagration. Facing enemies on all sides, it will be up to Commander Gray Pierce and Sigma Force to unravel a mystery going back millennia--and uncover the truth about a lost civilization and an arcane treasure that could save the planet...or destroy it"--